Making sense of hijāb and niqāb in contemporary Western societies - Solihu, Abdul Kabir Hussain (IIUM Press, 2009)
Ḥijāb, an Islamic ethico-religious and socio-cultural symbol, is increasingly becoming visible in the Western public arena giving rise to a debate over its compatibility with dominant Western culture and values. Placing it in an argumentative genre, the paper highlights the sociological, religious and cultural rationales for the increasing visibility of the Islamic dress code among young Muslim women. It provides a discursive framework based on a cultural sociology through which ḥijāb and niqāb could be accepted.